ANALYSIS OF EMPLOYEE JOB SATISFACTION IN FOOD & BEVERAGE SERVICE AT INTERCONTINENTAL BALI RESORT - A.A. Ayu Oka Mirah Wahyuni; Mahendra Adi Winatha; Hilda Apriani; I Gusti Ngurah Agung Suprastayasa (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2020)
Many studies have demonstrated a large impact on the job satisfaction and the way it influences productivity of employee or staff performance in order to increase hotel performance. This research is focused on analyzing employee job satisfaction level at InterContinental Bali Resort using Gruneberg Job Satisfaction Model as main theory. The data on this study gathered by distributing questionnaires and conducting interviews. After that, the result of it will be analyzed in quantitative and qualitative methods. The result from the research is most employees in Food & Beverage Service at Intercontinental Bali Resort are satisfied with the indicators stated by Gruneberg theory, however some improvements was addressed and findings were discussed.